The Best Web-Based Set Top Box (STB) Determination System Using The Analytical Hierarchy Process (AHP) Method - Ivan Wisnu Sanjaya; Abdi Pandu Kusuma; Filda Febrinita (JOSAR (Journal of Students Academic Research), 2025)
The transition from analog to digital television requires the public to use set top box (STB) devices in order to receive digital broadcasts. However, many users struggle to choose an set top box that suits their location and specific needs. This study aims to determine the best location-based set top box recommendations using the Analytical Hierarchy Process (AHP) method. AHP was chosen because it is capable of systematically processing comparisons of criteria such as chipset, brand, price, and features. Primary data was collected through surveys and interviews with technicians in Blitar City, while secondary data was obtained from journals and technical documentation. The results of the study indicate that the brand criterion holds the highest weight, followed by chipset, features, and price. Set top box with Sunplus chipsets demonstrated the best performance in areas with weak signals. The web-based system was developed using JavaScript, and the calculations were supported by Python to verify accuracy. Therefore, the AHP method is highly effective in providing optimal set top box recommendations based on location and user needs, while also serving as a digital education tool for the community. This system is expected to assist both the public and technicians in improving the quality of digital TV signal reception as an alternative solution. Based on the research results, the developed web-based system provides convenience for users in determining the best set top box according to the required location. The website is equipped with location input forms, internet feature preferences, and detailed score calculation features for each set top box brand, with varying output values. This white box testing successfully validated the implementation of the Analytical Hierarchy Process (AHP) for calculating the score of the set top box (STB). The test confirmed that the scoring function accurately produced the correct total score of 0.6673 for the GX6605 STB. This successful execution demonstrates the reliability and correctness of the system's decision-making process.